2018
DOI: 10.1111/aos.13801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of unique proteins in vitreous fluid of patients with noninfectious uveitis

Abstract: High-throughput proteomic and pathway analyses have exposed the potential association of these proteins with autoimmune pathogenesis in uveitis. The exact role of most of the proteins in autoimmune uveitis is yet to be unfurled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…On the contrary, Rao et al found that the diagnostic ability of the vessel density parameters of OCTA was only moderate 27. Another study revealed that cpVD is useful for differentiating moderate and advanced glaucoma, while MBR-T is useful for identifying early glaucoma 29. These previous reports are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, Rao et al found that the diagnostic ability of the vessel density parameters of OCTA was only moderate 27. Another study revealed that cpVD is useful for differentiating moderate and advanced glaucoma, while MBR-T is useful for identifying early glaucoma 29. These previous reports are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…It does not not measure IOP directly but curvature changes of the limbal cornea which are related to IOP variation and are therefore considered representative of IOP changes 30. Recently, Vitish-Sharma et al31 demonstrated a weak correlation between the Sensimed Triggerfish contact lens sensor data output and IOP measurements taken using the Tonopen XL applanation tonometer.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized multicenter clinical trial of 105 patients (141 cases), found 18% (with an additional 30% lost to follow-up presumably due to chalazia resolving) had complete resolution after warm compresses treatment with or without the addition of topical antibiotic or antibiotic steroid combination; despite similar outcomes, patients had higher satisfaction if they were given prescription medication 15. Of the cases that completely resolved, 86% resolved within 6 months; chalazia that resolved fully took less time than those which partially resolved (1.5 vs 2.2 months) 15. If chalazia were present for greater than 2 months, then they were more likely to benefit from the initial procedure being more invasive 15.…”
Section: Discussionmentioning
confidence: 99%
“…Of the cases that completely resolved, 86% resolved within 6 months; chalazia that resolved fully took less time than those which partially resolved (1.5 vs 2.2 months) 15. If chalazia were present for greater than 2 months, then they were more likely to benefit from the initial procedure being more invasive 15. Jackson et al noted that treatment success was 29% with warm compresses and chloramphenicol ointment within 3 months versus 72% after I&C 16.…”
Section: Discussionmentioning
confidence: 99%